HUBUNGAN DAN PENGARUH BIMBINGAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA SMA KAFAH UNGGUL TANGERANG - Denny Erica (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2016)
This study aims to find answers and explain the influence of tutoring onthe learning achievement of students, analyzing the variables that most influencethe learning achievements of learners, and to analyze the relationship betweendimensions variable tutoring the dimensions variable learning achievement ofstudents in high school Kafah Unggul Tangerang.This research method is amethod of quantitative approach that analyzes the research data to test or testcorrelation coefficient r. The results obtained r count of 0,478, while r table atsignificance level of 5% is 0,361 so that r count > of r table. From thecalculation, t count equal to 2.880 further than the price t table at significancelevel of 5% and db = n-2. So db is 30-2 = 28. Then the obtained t table atsignificant level 5% = 1,701. Turns t > t table. Based on the above dataprocessing r count 0,478 > 0,361 tables of r so that Ha is accepted. This meansthere is a significant relationship between tutoring and academic achievement ofstudents in high school Kafah Unggul Tangerang is included in the mediumcategory, because in the range between 0.400 to 0.599 is 0.478. An importantfinding of this study was the achievement of learners in high school Kafah UnggulTangerang, influenced by tutoring in the medium category that needs to beimproved variable tutoring is to maintain the continuity of the learningachievement of students in high school Kafah Unggul Tangerang.